Massive splenic infarction secondary to compression of splenic vessels by a pancreatic cystic tumor - Morgade, Paula; Fraga, Sebastián (Revista Argentina de Cirugía, 2022)
Splenic infarctions, a rare cause of abdominal pain, may be due to several conditions. We report the case of a male patient with a massive splenic infarction secondary to extrinsic compression from a pancreatic cystic tumor.